Pengaruh Green Brand Positioning, Green Brand Attitude, Green Brand Knowledge Terhadap Green Purchase Intention - Evan Himawan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this paper is to explore the direct and indirect influence of green brand positioning, green brand attitude and green brand knowledge on green purchase intention. Data were collected from 199 respondents. “green brand positioning” measure used five-item scale, “green brand attitude” measured used six-item scale, “green brand knowledge” and “green purchase intention” measure used five-item scale. All measurement items were measured on five point Linkert-type scales. The three hypotheses in this paper have been tested. green brand positioning significantly gives positive influence to green purchase intention. Green brand attitude significantly gives positive influence to green purchase intention and green brand knowledge significantly gives positive influence to green purchase intention.